Extraction of aniline from wastewater: equilibria, model, and fitting of apparent extraction equilibrium constants. Issue 8 (14th January 2016) - Chai, Wenshuai; Zhu, Xinyan; Liu, Wei; Zhang, Weidong; Zhou, Zhiyong; Ren, Zhongqi
Abstract : Reactive extraction complexes of aniline to D2EHPA or P507 in various diluents are obtained by the fitting equilibrium models presented. Abstract : The physical and reactive extraction equilibria of aniline at 298.2 ± 0.5 K were studied. n -Butylacetate (BA), n -decanol, n -heptane and methyl tert -butyl ether (MTBE) were used for physical extraction. The distribution coefficient ( D ) of aniline follows the sequence BA > MTBE > n -decanol > n -heptane. The largest distribution coefficient ( D = 22.58) can be obtained with BA owing to its strong polarity. The equilibrium temperature almost has no effect on the distribution coefficient except for MTBE. Tributyl phosphate (TBP), acetamide (N503), trialkylamine (N235), di-(2-ethylhexyl) phosphoric acid (D2EHPA) and (2-ethylhexyl) 2-ethylhexylphosphanate (P507) were used as extractants with BA, kerosene and n -heptane as diluents for the reactive extraction. TBP, N503 and N235 show weak removal abilities because of their neutral and basic characteristics. For the acidic phosphorus-containing extractants, namely, D2EHPA and P507, equilibrium models are presented that employ the mass action law and used to determine model parameters and apparent extraction equilibrium constants ( K 11, K 12, and K 21 ). The reactive extraction complexes are considered as 1 : 1 and 1 : 2 aniline to D2EHPA complexes with BA as diluent, 1 : 2 aniline to D2EHPA complexes with kerosene and n -heptane as diluents, and 1 : 1 and 1 : 2 aniline to P507 complexes with kerosene and n -heptane as diluents. The distribution coefficients and loadings of D2EHPA and P507 calculated using the equilibrium model parameters and apparent extraction equilibrium constants efficiently agree with the experimental data, which indicates that the models are valid in representing the equilibrium behavior of aniline with the selected extractants in reactive extraction. The effects of temperature on extraction abilities were investigated and the enthalpy change of the extraction process with D2EHPA in kerosene was obtained.